The first open public space in Krasnoyarsk - Blyankinshtein, Olga; Popkova, Natalya (project baikal, 2021)
Krasnoyarsk parks are studied in the general system of green areas of the city. The Central Park of Krasnoyarsk is analyzed in detail, its evolution is traced through its periods. The planning, landscape and architectural-spatial transformations of the garden-park territory have been studied and illustrated. The prospects for the development of the park are outlined on the basis of a review of project proposals and the results of an Open International Competition for the development concept of Gorky Central Park in Krasnoyarsk in 2020. The principles of a good park have been formulated.